Robotic Single-Port da Vinci Surgical System (SP1098) in Gynecologic Surgery: A Systematic Review of Literature - Martina Arcieri; Paola Romeo; Giuseppe Vizzielli; Stefano Restaino; Lorenza Driul; Guglielmo Stabile; Roberta Granese; Stefano Cianci; Alfredo Ercoli (Clinical and Experimental Obstetrics & Gynecology)
Background: Recently, new surgical systems less invasive than standard laparoscopy have been developed. Among these, robotic single site surgery is playing a pivotal role. In this field, the da Vinci SP (Single-Port) Surgical System (SP1098) is one of the newest surgical technology that presents innovative characteristics that may lead to better surgical outcomes. Few groups have already published their experience and results with this system in gynecology. Methods: The aim of the present systematic review was to provide a comprehensive overview of the status and applications of da Vinci SP1098 in gynecologic surgery. A systematic review of the literature was performed. Studies were identified until September 2022. Results: Six studies were included, reporting a total of 211 patients. The indication for surgery was both benign and malignant disorders. In terms of operative outcomes, the mean/median docking time varied from 2.1 to 5 min while mean/median operating time from 86.5 to 245 min. There was no conversion to multi-port laparoscopy or laparotomy and no major complications related to SP surgery. Conclusions: In conclusion, the preliminary and limited data available regarding the da Vinci SP1098 Surgical System suggest the technical feasibility and safety for its use in gynecologic surgery, with minimal alteration of the surgical technique.